Quality improvement for HIV screening in a primary care resident clinic - Tracey Doering; Sagal Mohamed; Laura Hollar; Zachary Pugh (Journal of Community Hospital Internal Medicine Perspectives, 2017)
Primary care physicians are responsible for the initiation of the preventive health screening tests and examinations for their patients. Resident physicians may be uncomfortable obtaining a sexual history from their patient. A performance improvement project was carried out in the resident clinic to see if we could improve HIV screening of our patients. With a cohesive effort between the faculty preceptors and residents, we were able to improve screening rates for HIV and improve some aspects, but not all, of sexual history taking for our population of patients. We identified two patients who screened positive for a rate of 1.4%. Abbreviations: CDC: